Toner for electrostatic charge image development
Patent Information
- Application Number
- JP2021215216
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-28
- Publication Date
- 2025-03-12
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0012】 本発明によれば、優れた低温定着性を有し、耐ホットオフセット性、細線再現性およびブレードクリーニング性にバランス良く優れ、高温放置後のトナー噴出しの発生が抑制された静電荷像現像用トナーを製造することができる。
Smart Images

Figure 2025032401000003 
Figure 2025032401000001 
Figure 2025032401000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner for developing electrostatic images, which is used for developing electrostatic latent images in electrophotography, electrostatic recording, electrostatic printing and the like. [Background technology]
[0002] 2. Description of the Related Art Image forming apparatuses such as electrophotographic apparatuses, electrostatic recording apparatuses, and electrostatic printing apparatuses widely employ a method of forming a desired image by developing an electrostatic latent image formed on a photoconductor with a toner for developing an electrostatic image, and this method is applied to copiers, printers, facsimiles, and multifunction machines thereof.
[0003] For example, in an electrophotographic device using electrophotography, the surface of a photoconductor made of a photoconductive material is generally uniformly charged by various means, an electrostatic latent image is then formed on the photoconductor, the electrostatic latent image is then developed using toner (developing process), and if necessary, the toner image is transferred to a recording material such as paper (transfer process), and the toner is then fixed to the recording material by heating or the like (fixing process) to obtain a printed matter.
[0004] Among the image forming processes, in the fixing process, it is usually necessary to heat the fixing roll to 150° C. or higher during fixing, and a large amount of electricity is consumed as an energy source. In response to this, in recent years, with the increasing demand for reducing energy consumption and increasing printing speed for the image forming apparatus, there is a demand for the design of a toner that can maintain a high fixing rate even at a low fixing temperature (a toner with excellent low-temperature fixing ability).
[0005] For example, Patent Document 1 proposes a toner containing toner particles that contain a binder resin and a crystalline material, in which, in powder dynamic viscoelasticity measurement, the onset temperature T(A) of storage modulus E' obtained when the temperature is increased at 20° C. / min and the onset temperature T(B) of storage modulus E' obtained when the temperature is increased at 5° C. / min satisfy the relationship T(A)-T(B)≦3.0° C., the peak temperature of the maximum endothermic peak in differential scanning calorimetry is 50.0 to 90.0° C., and the content of tetrahydrofuran insoluble matter in the binder resin is in the range of 15 to 60 mass %. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2021-5050 Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, there has been an increasing demand for further reduction in energy consumption and further increase in printing speed, and in order to achieve these, there is a demand for further improvement in low-temperature fixability while maintaining sufficient fine-line reproducibility and blade cleaning properties. According to the present inventor's investigation, it was found that the toner described in Patent Document 1 needs further improvement. The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for producing a toner for developing electrostatic images, which has excellent low-temperature fixing properties, a well-balanced excellent hot offset resistance, fine-line reproducibility and blade cleanability, and which suppresses the occurrence of toner ejection after being left at high temperatures. [Means for solving the problem]
[0008] The present inventors have conducted studies to achieve the above-mentioned object, and have found that in a toner for developing electrostatic images containing colored resin particles containing a binder resin, a colorant, a charge control agent, and a crystalline material, the above-mentioned object can be achieved by making the colored resin particles constituting the toner for developing electrostatic images have a specific microstructure, specifically, by setting the total area ratio of crystalline material domains and the number of crystalline material domains in the cross section of the colored resin particle, obtained by observing the cross section of the colored resin particle using a reflected electron image of a scanning electron microscope, within specific ranges, and have thus completed the present invention.
[0009] That is, according to the present invention, there is provided a toner for developing electrostatic images, which contains a binder resin, a colorant, a charge control agent, and colored resin particles containing a crystalline material, The toner for developing electrostatic images is provided, in which, when a cross section of the colored resin particle is observed using a backscattered electron image of a scanning electron microscope, the total area ratio of the domains of the crystalline material in the cross section of the colored resin particle is 10 to 30%, and the number of domains of the crystalline material present in the cross section of the colored resin particle is in the range of 10 to 40 on average per particle.
[0010] In the toner for developing electrostatic images of the present invention, when a cross section of the colored resin particle is observed using a reflected electron image of a scanning electron microscope, it is preferable that the average circularity of the domains of the crystalline material in the cross section of the colored resin particle is 0.50 or less. In the toner for developing electrostatic images of the present invention, when a cross section of the colored resin particle is observed using a reflected electron image of a scanning electron microscope, it is preferable that the average ratio of the minor axis to the major axis of the domain of the crystalline material in the cross section of the colored resin particle is 0.60 or less. In the electrostatic image developing toner of the present invention, the content of the crystalline material is preferably 5.0 to 40.0 parts by mass with respect to 100 parts by mass of the binder resin. In the electrostatic image developing toner of the present invention, the crystalline material is preferably an ester wax having a number average molecular weight (Mn) of 500 to 1,550.
[0011] In the toner for developing electrostatic images of the present invention, it is preferable that the colored resin particles further contain an additive having a polydiene structure. In the toner for developing electrostatic images of the present invention, the binder resin is preferably a styrene-(meth)acrylic acid ester copolymer. The toner for developing electrostatic images of the present invention is preferably a positively charged toner. The toner for developing electrostatic images of the present invention is preferably produced by a pulverization method or a suspension polymerization method. Effect of the Invention
[0012] According to the present invention, it is possible to produce a toner for developing electrostatic images which has excellent low-temperature fixing properties, a well-balanced excellent hot offset resistance, fine line reproducibility and blade cleanability, and which is inhibited from spewing out of the toner after being left at high temperatures. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional photograph of a colored resin particle in Example 6, taken as a backscattered electron image by a scanning electron microscope (FE-SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The toner for developing electrostatic images of the present invention (hereinafter, sometimes simply referred to as "toner") is a toner for developing electrostatic images containing a binder resin, a colorant, a charge control agent, and colored resin particles containing a crystalline material, When the cross section of the colored resin particle is observed using a backscattered electron image of a scanning electron microscope, the total area ratio of the domains of the crystalline material in the cross section of the colored resin particle is 10 to 30%, and the number of domains of the crystalline material present in the cross section of the colored resin particle is in the range of 10 to 40 on average per particle.
[0015] First, the colored resin particles constituting the toner of the present invention will be described. The colored resin particles constituting the toner of the present invention can be produced, for example, by a dry method such as a pulverization method, or a wet method such as an emulsion polymerization aggregation method, a dispersion polymerization method, a suspension polymerization method, a dissolution suspension method, etc. As the colored resin particles constituting the toner of the present invention, those obtained by a pulverization method, which is an example of a dry method, can be suitably used. A method for producing colored resin particles constituting the toner of the present invention by a pulverization method, which is an example of a dry method, will be described below.
[0016] In the pulverization method, first, a binder resin, a colorant, a charge control agent, and a crystalline material, as well as other additives that are added as necessary, are kneaded while being heated using a mixer, and the resulting kneaded product is coarsely pulverized and finely pulverized, and then classified into the desired particle size using a classifier, thereby obtaining pulverized colored resin particles.
[0017] The binder resin is not particularly limited, but examples thereof include polystyrene resin, polyester resin, styrene-(meth)acrylic acid ester copolymer (meaning "styrene-acrylic acid ester copolymer and / or styrene-methacrylic acid ester copolymer"), styrene-acrylonitrile copolymer, styrene-butadiene copolymer, styrene-maleic anhydride copolymer, polyethylene resin, polypropylene resin, etc. The binder resin may be used alone or in combination of two or more. Among these, from the viewpoint of further improving low-temperature fixability, styrene-(meth)acrylic acid ester copolymer and polyester resin are preferred, styrene-(meth)acrylic acid ester copolymer is more preferred, and styrene-acrylic acid ester copolymer is even more preferred.
[0018] Examples of (meth)acrylic acid esters constituting the styrene-(meth)acrylic acid ester copolymer include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, dimethylaminoethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, and dimethylaminoethyl methacrylate. These (meth)acrylic acid esters may be used alone or in combination of two or more. Among these, ethyl acrylate, propyl acrylate, and butyl acrylate are preferred, and n-butyl acrylate is more preferred.
[0019] The content of styrene units in the styrene-(meth)acrylic acid ester copolymer is preferably 60 to 90 mass%, more preferably 65 to 85 mass%, and even more preferably 70 to 80 mass%, and the content of (meth)acrylic acid ester monomer units is preferably 10 to 40 mass%, more preferably 15 to 35 mass%, and even more preferably 20 to 30 mass%.
[0020] The glass transition temperature of the binder resin is preferably 40 to 80° C., more preferably 45 to 70° C., and further preferably 50 to 60° C. By setting the glass transition temperature within the above range, the low-temperature fixability can be more appropriately improved. The glass transition temperature of the binder resin can be determined, for example, in accordance with ASTM D3418-82.
[0021] As the colorant, for example, when producing a color toner (usually, four types of toner are used: black toner, cyan toner, yellow toner, and magenta toner), a black colorant, a cyan colorant, a yellow colorant, and a magenta colorant can be used, respectively.
[0022] As the black colorant, for example, pigments and dyes such as carbon black, titanium black, and magnetic powders such as zinc iron oxide and nickel iron oxide can be used.
[0023] Examples of cyan colorants include copper phthalocyanine pigments, their derivatives, and anthraquinone pigments and dyes. Specific examples include CI Pigment Blue 2, 3, 6, 15, 15:1, 15:2, 15:3, 15:4, 16, 17:1, 60, etc.
[0024] Examples of the yellow colorant include azo pigments such as monoazo pigments and disazo pigments, condensed polycyclic pigments, dyes, and other compounds. Specific examples include CI Pigment Yellow 3, 12, 13, 14, 15, 17, 62, 65, 73, 74, 83, 93, 97, 120, 138, 151, 155, 180, 181, 185, 186, 214, 219, CI Solvent Yellow 98, 162, and the like.
[0025] Examples of magenta colorants include monoazo pigments, azo pigments such as disazo pigments, condensed polycyclic pigments, dyes, and other compounds. Specific examples include CI Pigment Red 31, 48, 57:1, 58, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 149, 150, 163, 170, 184, 185, 187, 202, 206, 207, 209, 238, 269, 251, CI Solvent Violet 31, 47, 59, and CI Pigment Violet 19.
[0026] The colorants may be used alone or in combination of two or more kinds. The amount of the colorant used is preferably 1 to 15 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 2 to 8 parts by mass, relative to 100 parts by mass of the binder resin.
[0027] The charge control agent is not particularly limited as long as it is generally used as a charge control agent for toner, but among the charge control agents, a positively or negatively charged charge control resin is preferred, and a positively charged one is more preferred, from the viewpoint that it has high compatibility with the binder resin and can impart stable chargeability (charge stability) to the toner particles, thereby improving the dispersibility of the colorant. That is, the toner of the present invention is more preferably a positively charged toner.
[0028] Positively charged charge control agents include nigrosine dyes, quaternary ammonium salts, triaminotriphenylmethane compounds, and imidazole compounds, as well as polyamine resins, quaternary ammonium group-containing copolymers, and quaternary ammonium base-containing copolymers, which are preferably used as charge control resins.
[0029] Examples of negatively chargeable charge control agents include azo dyes containing metals such as Cr, Co, Al, and Fe, metal salicylate compounds, and metal alkylsalicylate compounds, as well as sulfonic acid group-containing copolymers, sulfonate salt group-containing copolymers, carboxylate group-containing copolymers, and carboxylate salt group-containing copolymers, which are preferably used as charge control resins.
[0030] The weight average molecular weight (Mw) of the charge control resin is in the range of 5,000 to 30,000, preferably in the range of 8,000 to 25,000, and more preferably in the range of 10,000 to 20,000, in terms of polystyrene, measured by gel permeation chromatography (GPC) using tetrahydrofuran.
[0031] Furthermore, the copolymerization ratio (functional group amount) of the monomer having a functional group such as a quaternary ammonium salt group or a sulfonate salt group in the charge control resin is preferably within the range of 0.5 to 12 mass%, more preferably within the range of 1.0 to 6 mass%, and even more preferably within the range of 1.5 to 5 mass%.
[0032] The content of the charge control agent is preferably 0.01 to 20 parts by mass, more preferably 0.03 to 10 parts by mass, and further preferably 0.03 to 8 parts by mass, relative to 100 parts by mass of the binder resin. By setting the amount of the charge control agent added within the above range, it is possible to effectively suppress the occurrence of fog and print stains while appropriately increasing the dispersibility of the colorant.
[0033] Examples of the crystalline material include a material that acts as a release agent for the toner and a material that improves fixability, such as a crystalline polyester resin and an ester wax. In the toner of the present invention, the crystalline material is present in the colored resin particles in a state where at least a part of the crystalline material forms a domain structure. The domain structure formed by the crystalline material will be described later.
[0034] The crystalline polyester resin may be, for example, a condensation polymer of an aliphatic diol and an aliphatic dicarboxylic acid, and the crystalline polyester resin is preferably a condensation polymer of an aliphatic diol having 2 to 12 carbon atoms and an aliphatic dicarboxylic acid having 2 to 12 carbon atoms.
[0035] Examples of the aliphatic diol having 2 to 12 carbon atoms include 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, etc. These may be used alone or in combination of two or more.
[0036] Examples of aliphatic dicarboxylic acids having 2 to 12 carbon atoms include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, and lower alkyl esters and acid anhydrides of these aliphatic dicarboxylic acids. These may be used alone or in combination of two or more.
[0037] An aromatic dicarboxylic acid can be used together with or instead of the aliphatic dicarboxylic acid having 2 to 12 carbon atoms. Examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid.
[0038] The crystalline polyester resin can be produced by a general polyester polymerization method, for example, by reacting a dicarboxylic acid component with a diol component, such as a direct polycondensation method or an ester exchange method.
[0039] The ester wax is not particularly limited, but is preferably an ester wax having a number average molecular weight (Mn) of 500 to 1550, and preferably a fatty acid ester compound having a number average molecular weight (Mn) of 500 to 1550. The fatty acid ester compound is preferably a product of an ester reaction between a monohydric alcohol and / or a polyhydric alcohol and a saturated fatty acid and / or an unsaturated fatty acid.
[0040] Specific examples of monohydric alcohols include monohydric saturated aliphatic alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 1-hexanol, octanol, 2-ethyl-1-hexanol, nonyl alcohol, lauryl alcohol, cetyl alcohol, stearyl alcohol, and behenyl alcohol; monohydric unsaturated aliphatic alcohols such as allyl alcohol, methallyl alcohol, crotyl alcohol, and oleyl alcohol; monohydric alicyclic alcohols such as cyclohexanol; and monohydric aromatic alcohols such as phenol, phenylmethanol (benzyl alcohol), methylphenol (cresol), p-ethylphenol, dimethylphenol (xylenol), nonylphenol, dodecylphenol, phenylphenol, and naphthol.
[0041] Specific examples of polyhydric alcohols include dihydric saturated aliphatic alcohols such as ethylene glycol and propylene glycol; dihydric aromatic alcohols such as catechol and hydroquinone; and trihydric or higher saturated aliphatic alcohols such as glycerin, pentaerythritol, dipentaerythritol, and polyglycerin.
[0042] Among these monohydric alcohols and polyhydric alcohols, monohydric to tetrahydric saturated aliphatic alcohols are preferred, behenyl alcohol and pentaerythritol are more preferred, and behenyl alcohol is particularly preferred.
[0043] The fatty acid used as the raw material for the fatty acid ester compound is preferably a saturated fatty acid and / or an unsaturated fatty acid having a carbon number of 12 to 22, more preferably a carbon number of 14 to 18. Among them, the saturated fatty acid having the above carbon numbers is particularly preferred because it is easy to obtain a fatty acid ester compound having a number average molecular weight (Mn) of 500 to 1550.
[0044] Specific examples of saturated fatty acids having the above carbon numbers include, but are not limited to, lauric acid (carbon number 12), myristic acid (carbon number 14), pentadecylic acid (carbon number 15), palmitic acid (carbon number 16), margaric acid (carbon number 17), stearic acid (carbon number 18), arachidic acid (carbon number 20), and behenic acid (carbon number 22). Among these saturated fatty acids, stearic acid (carbon number 18), arachidic acid (carbon number 20), and behenic acid (carbon number 22) are preferred, and stearic acid (carbon number 18) is more preferred.
[0045] Specific examples of unsaturated fatty acids include, but are not limited to, the following compounds: Palmitoleic acid (CH3(CH2)5CH=CH(CH2)7COOH) Oleic acid (CH3(CH2)7CH=CH(CH2)7COOH) Vaccenic acid (CH3(CH2)5CH=CH(CH2)9COOH) Linoleic acid (CH3(CH2)3(CH2CH=CH)2(CH2)7COOH) (9,12,15)-Linolenic acid (CH3(CH2CH=CH)3(CH2)7COOH) (6,9,12)-Linolenic acid (CH3(CH2)3(CH2CH=CH)3(CH2)4COOH) Eleostearic acid (CH3(CH2)3(CH=CH)3(CH2)7COOH) Arachidonic acid (CH3(CH2)3(CH2CH=CH)4(CH2)3COOH)
[0046] The saturated fatty acids and / or unsaturated fatty acids may be used alone or in combination of two or more.
[0047] The fatty acid ester compounds as described above can be produced according to a conventional method. For example, a method of producing such fatty acid ester compounds includes a method of carrying out an ester reaction using a monohydric alcohol and / or a polyhydric alcohol and a saturated fatty acid and / or an unsaturated fatty acid. In addition, a commercially available fatty acid ester compound can be used as the fatty acid ester compound, and examples of the commercially available fatty acid ester compound include "WEP2", "WEP3", "WEP4", "WEP5", "WE6", and "WE11" (all of which are product names) manufactured by NOF Corporation.
[0048] The number average molecular weight (Mn) of the fatty acid ester compound is preferably 500 to 1550, more preferably 550 to 1200, and further preferably 550 to 1100. The number average molecular weight (Mn) of the fatty acid ester compound can be measured, for example, in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran.
[0049] As the crystalline material, other crystalline materials may be used in place of the above-mentioned crystalline polyester resin and ester wax, or together with the crystalline polyester resin or ester wax, and examples of such other crystalline materials include low molecular weight polyolefin waxes and modified waxes thereof, natural plant waxes such as jojoba, petroleum waxes such as paraffin, mineral waxes such as ozokerite, synthetic waxes such as Fischer-Tropsch wax, polyhydric alcohol esters such as dipentaerythritol esters, etc. These may be used alone or in combination of two or more.
[0050] From the viewpoint of further improving the low-temperature fixing property of the resulting toner, the melting point of the crystalline material is preferably 50 to 90°C, more preferably 60 to 90°C, even more preferably 65 to 80°C, particularly preferably 68 to 80°C, and most preferably 70 to 80°C.
[0051] The content of the crystalline material is preferably 5.0 to 40.0 parts by mass, more preferably 10 to 35 parts by mass, and further preferably 15 to 30 parts by mass, relative to 100 parts by mass of the binder resin. By setting the content of the crystalline material within the above range, it is possible to further improve low-temperature fixability while making the particle size distribution of the obtained toner relatively uniform.
[0052] The colored resin particles may further contain an additive having a polydiene structure. By using such an additive having a polydiene structure, the compatibility of the additive having a polydiene structure with the crystalline material makes it possible to increase the dispersibility of the crystalline material in the colored resin particles, thereby making it possible to more suitably form a domain structure of the crystalline material described later in the colored resin particles.
[0053] The additive having a polydiene structure is not particularly limited, and examples thereof include conjugated diene-aromatic vinyl thermoplastic elastomers, which are polymers having structural units derived from a conjugated diene compound and structural units derived from an aromatic vinyl compound; conjugated diene elastomers such as polybutadiene rubber and polyisoprene rubber; and the like. Of these, conjugated diene-aromatic vinyl thermoplastic elastomers are preferred, and among the conjugated diene-aromatic vinyl thermoplastic elastomers, unhydrogenated conjugated diene-aromatic vinyl thermoplastic elastomers are particularly preferred.
[0054] Examples of the conjugated diene-aromatic vinyl thermoplastic elastomer include random, block, graft and other copolymers of a conjugated diene monomer, an aromatic vinyl monomer, and, if necessary, other monomers copolymerizable therewith, and hydrogenated products of such copolymers.
[0055] Such a conjugated diene-aromatic vinyl thermoplastic elastomer is not particularly limited, but from the viewpoint of further improving the low-temperature fixing property of the toner, a block copolymer containing at least one aromatic vinyl polymer block and at least one conjugated diene polymer block can be preferably used.
[0056] Hereinafter, a block copolymer containing at least one aromatic vinyl polymer block and at least one conjugated diene polymer block (hereinafter, sometimes simply referred to as "block copolymer"), which is a representative example of a conjugated diene-aromatic vinyl thermoplastic elastomer, will be described. The block copolymer used in the present invention contains at least one aromatic vinyl polymer block obtained by polymerizing an aromatic vinyl monomer and at least one conjugated diene polymer block obtained by polymerizing a conjugated diene monomer.
[0057] The aromatic vinyl monomer is not particularly limited as long as it is an aromatic vinyl compound, and examples thereof include styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-t-butylstyrene, 5-t-butyl-2-methylstyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, 2-methyl-4,6-dichlorostyrene, 2,4-dibromostyrene, and vinylnaphthalene. Among these, it is preferable to use styrene. These aromatic vinyl monomers can be used alone or in combination of two or more in each aromatic vinyl polymer block. In addition, when the block copolymer has a plurality of aromatic vinyl polymer blocks, each aromatic vinyl polymer block may be composed of the same aromatic vinyl monomer unit or may be composed of different aromatic vinyl monomer units.
[0058] The aromatic vinyl polymer block may contain other monomer units as long as the aromatic vinyl monomer unit is the main repeating unit. Examples of other monomers that can be used in the aromatic vinyl polymer block include conjugated diene monomers such as 1,3-butadiene and isoprene (2-methyl-1,3-butadiene), α,β-unsaturated nitrile monomers, unsaturated carboxylic acid or acid anhydride monomers, unsaturated carboxylic acid ester monomers, and non-conjugated diene monomers. The content of monomer units other than aromatic vinyl monomer units in the aromatic vinyl polymer block is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably substantially 0% by mass.
[0059] The conjugated diene monomer is not particularly limited as long as it is a conjugated diene compound, and examples thereof include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, and 1,3-hexadiene. Among these, from the viewpoint of high effect of improving low-temperature fixability, it is preferable to use 1,3-butadiene and / or isoprene, and it is particularly preferable to use isoprene. These conjugated diene monomers can be used alone or in combination of two or more in each conjugated diene polymer block. In addition, when the block copolymer has a plurality of conjugated diene polymer blocks, each conjugated diene polymer block may be composed of the same conjugated diene monomer unit or may be composed of different conjugated diene monomer units. Furthermore, a hydrogenation reaction may be performed on a part of the unsaturated bonds of each conjugated diene polymer block.
[0060] The conjugated diene polymer block may contain other monomer units as long as the conjugated diene monomer unit is the main repeating unit. Examples of other monomers that can be used in the conjugated diene polymer block include aromatic vinyl monomers such as styrene and α-methylstyrene, α,β-unsaturated nitrile monomers, unsaturated carboxylic acid monomers, unsaturated carboxylic anhydride monomers, unsaturated carboxylic ester monomers, and non-conjugated diene monomers. The content of monomer units other than the conjugated diene monomer units in the conjugated diene polymer block is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably substantially 0% by mass.
[0061] The vinyl bond content of the conjugated diene polymer block (the ratio of 1,2-vinyl bond units and 3,4-vinyl bond units to all conjugated diene monomer units in the conjugated diene polymer block) is not particularly limited, but is preferably 1 to 20 mol%, more preferably 2 to 15 mol%, and particularly preferably 3 to 10 mol%.
[0062] The block copolymer is not particularly limited in the number of each polymer block and the bonding form thereof, so long as it contains at least one aromatic vinyl polymer block and at least one conjugated diene polymer block. Specific examples of block copolymers include the following. In the following specific examples, Ar represents an aromatic vinyl polymer block, D represents a conjugated diene polymer block, X represents a residue of a coupling agent, and n represents an integer of 2 or more. (a) Aromatic vinyl-conjugated diene block copolymer represented as Ar-D (b) Aromatic vinyl-conjugated diene-aromatic vinyl block copolymers represented as Ar-D-Ar and / or (Ar-D)nX (c) conjugated diene-vinyl aromatic-conjugated diene block copolymers represented as D-Ar-D and / or (D-Ar)nX (d) an aromatic vinyl-conjugated diene-aromatic vinyl-conjugated diene block copolymer represented as Ar-D-Ar-D; (e) A block copolymer composition comprising any combination of two or more of the above (a) to (d).
[0063] As the block copolymer, it is preferable to use one containing at least the aromatic vinyl-conjugated diene block copolymer represented by (a) Ar-D, and it is more preferable to use one containing at least the aromatic vinyl-conjugated diene block copolymer represented by (a) Ar-D and the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by (b) Ar-D-Ar and / or (Ar-D)nX. The content of the aromatic vinyl-conjugated diene block copolymer represented by Ar-D (i.e., a diblock copolymer consisting of an aromatic vinyl polymer block and a block of a polymer copolymerizable with the aromatic vinyl polymer) in the conjugated diene-aromatic vinyl thermoplastic elastomer is preferably 40% by mass (weight %) or more, preferably 50% by mass or more, and more preferably 55% by mass or more. The upper limit is not particularly limited, but is preferably 98% by mass or less, and more preferably 95% by mass or less. By setting the content of the aromatic vinyl-conjugated diene block copolymer represented by Ar-D (i.e., a diblock copolymer consisting of an aromatic vinyl polymer block and a block of a polymer copolymerizable with the aromatic vinyl polymer) in the conjugated diene-aromatic vinyl thermoplastic elastomer to 40 mass% or more, it is possible to further improve the dispersibility in the colored resin particles and the compatibility with crystalline materials.
[0064] In the aromatic vinyl-conjugated diene block copolymer represented by Ar-D, the weight average molecular weight (Mw(Ar)) of the aromatic vinyl polymer block Ar is not particularly limited, but is preferably 10,000 to 50,000, more preferably 15,000 to 30,000, and the weight average molecular weight (Mw(D)) of the conjugated diene polymer block D is not particularly limited, but is preferably 50,000 to 200,000, more preferably 60,000 to 150,000.
[0065] In the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar and / or (Ar-D)nX, the weight average molecular weight (Mw(Ar)) of the aromatic vinyl polymer block Ar is not particularly limited, but is preferably 20,000 to 70,000, more preferably 25,000 to 50,000, and the weight average molecular weight (Mw(D)) of the conjugated diene polymer block D is not particularly limited, but is preferably 100,000 to 300,000, more preferably 120,000 to 250,000. The weight average molecular weights are all values calculated as polystyrene equivalents measured by gel permeation chromatography (GPC) using tetrahydrofuran.
[0066] The content ratio of the aromatic vinyl monomer units in the block copolymer relative to the total monomer units is preferably 10 to 30 mass%, more preferably 12 to 25 mass%, and even more preferably 15 to 25 mass%. By setting the content ratio of the aromatic vinyl monomer units within the above range, it is possible to further increase the dispersibility in the colored resin particles and the compatibility with the crystalline material.
[0067] In the case where all polymer components constituting the block copolymer are composed only of aromatic vinyl monomer units and conjugated diene monomer units, the content of aromatic vinyl monomer units in the block copolymer can be easily measured by subjecting the block copolymer to ozonolysis and then reduction with lithium aluminum hydride according to the method described in Rubber Chem. Technol., 45, 1295 (1972), whereby the conjugated diene monomer unit portion is decomposed and only the aromatic vinyl monomer unit portion can be isolated, so that the total aromatic vinyl monomer unit content can be easily measured.
[0068] The weight average molecular weight (Mw) of the aromatic vinyl monomer unit in the block copolymer is not particularly limited, but is preferably 10,000 to 50,000, more preferably 20,000 to 40,000, in terms of polystyrene measured by gel permeation chromatography (GPC) using tetrahydrofuran. The weight average molecular weight (Mw) of the conjugated diene monomer unit in the block copolymer is not particularly limited, but is preferably 50,000 to 200,000, more preferably 60,000 to 180,000.
[0069] The melt index (MI) of the block copolymer is not particularly limited, but is selected, for example, from the range of 1 to 1000 g / 10 min, and preferably from 5 to 30 g / 10 min, as a value measured in accordance with ASTM D-1238 (G condition, 200° C., 5 kg).
[0070] The block copolymer used in the present invention can be produced by a conventional method. For example, a method of producing such a block copolymer includes a method of sequentially polymerizing an aromatic vinyl monomer and a conjugated diene monomer by an anionic living polymerization method to form a polymer block, and then reacting a coupling agent to perform coupling, if necessary.
[0071] In addition, when the block copolymer used in the present invention contains at least the aromatic vinyl-conjugated diene block copolymer represented by (a) Ar-D and the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by (b) Ar-D-Ar and / or (Ar-D)X, the following method can be adopted.
[0072] That is, first, an aromatic vinyl monomer is polymerized by an anionic living polymerization method, and then a conjugated diene monomer is added and polymerized to obtain a diblock copolymer having an active end. Next, a coupling agent less than 1 molar equivalent is added to the active end of the diblock copolymer having an active end, and a part of the diblock copolymer having an active end is subjected to a coupling reaction to obtain an aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented as (Ar-D)nX, and then a polymerization terminator is added to inactivate the remaining diblock copolymer having an active end to obtain a diblock copolymer represented as Ar-D. In this case, a bifunctional coupling agent such as dichlorosilane, monomethyldichlorosilane, dimethyldichlorosilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dichloroethane, dibromoethane, methylene chloride, and dibromomethane can be used as the coupling agent to obtain an aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented as Ar-D-Ar (D includes a residue of the coupling agent).
[0073] The content ratio of the aromatic vinyl-conjugated diene block copolymer represented by (a) Ar-D and the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by (b) Ar-D-Ar and / or (Ar-D)nX is not particularly limited, but the content ratio of the aromatic vinyl-conjugated diene block copolymer represented by (a) Ar-D is preferably 10 to 90 mass%, more preferably 20 to 80 mass%. The content ratio of the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by (b) Ar-D-Ar and / or (Ar-D)nX is preferably 10 to 90 mass%, more preferably 20 to 80 mass%.
[0074] In addition, as the conjugated diene-aromatic vinyl thermoplastic elastomer, a random copolymer of an aromatic vinyl monomer and a conjugated diene monomer can be used instead of the above-mentioned block copolymer. The random copolymer of an aromatic vinyl monomer and a conjugated diene monomer can be produced by living anionic polymerization using, for example, an organic alkali metal compound as a polymerization initiator. Examples of the organic alkali metal compound include organic lithium compounds, organic sodium compounds, and organic potassium compounds. Specifically, organic monolithium compounds such as n-butyl lithium, sec-butyl lithium, t-butyl lithium, hexyl lithium, phenyl lithium, and stilbene lithium; organic polyvalent lithium compounds such as dilithiomethane, 1,4-dilithiobutane, 1,4-dilithio-2-ethylcyclohexane, 1,3,5-trilithiobenzene, and 1,3,5-tris(lithiomethyl)benzene; organic sodium compounds such as sodium naphthalene; and organic potassium compounds such as potassium naphthalene. Among these organic metal compounds, n-butyl lithium is preferably used.
[0075] In the random copolymer of an aromatic vinyl monomer and a conjugated diene monomer, the content ratio of the aromatic vinyl monomer unit to the total monomer units is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less. By setting the content ratio of the aromatic vinyl monomer unit within the above range, it is possible to highly balance the affinity of the random copolymer to the crystalline material and the affinity of the block copolymer to the binder resin, and the obtained toner can have excellent low-temperature fixing properties.
[0076] Furthermore, in the present invention, conjugated diene elastomers such as polybutadiene rubber and polyisoprene rubber can also be suitably used as additives having a polydiene structure. Conjugated diene elastomers such as polybutadiene rubber and polyisoprene rubber can be produced, for example, by living anionic polymerization using an organic alkali metal compound as a polymerization initiator. As the organic alkali metal compound, for example, the above-mentioned compounds can be used.
[0077] The weight average molecular weight (Mw) of the additive having a polydiene structure is not particularly limited, but is preferably 60,000 to 350,000, more preferably 80,000 to 250,000, in terms of polystyrene measured by gel permeation chromatography (GPC) using tetrahydrofuran. By setting the weight average molecular weight (Mw) within the above range, the low temperature fixability of the obtained toner can be further improved.
[0078] The content of the additive having a polydiene structure is preferably 0.5 to 20 parts by mass, more preferably 1.0 to 15 parts by mass, and even more preferably 3 to 7 parts by mass, relative to 100 parts by mass of the binder resin. By setting the content of the additive having a polydiene structure within the above range, the low temperature fixability of the obtained toner can be further improved.
[0079] The content of the additive having a polydiene structure relative to the content of the crystalline material is preferably 0.02 to 0.75, more preferably 0.10 to 0.55, and even more preferably 0.20 to 0.50, in terms of the weight ratio of "content of additive having a polydiene structure / content of crystalline material". By setting the content of the additive having a polydiene structure within the above range, the low temperature fixability of the obtained toner can be further improved.
[0080] The colored resin particles may further contain a polar resin. The polar resin is not particularly limited, but an acrylic resin can be suitably used. The acrylic resin is a copolymer (acrylate copolymer) whose main component is at least one of an acrylic acid ester and a methacrylic acid ester, and at least one of an acrylic acid and a methacrylic acid. The acid monomer is preferably acrylic acid.
[0081] Examples of the acrylic resin include copolymers of an acrylic acid ester and acrylic acid, copolymers of an acrylic acid ester and methacrylic acid, copolymers of a methacrylic acid ester and acrylic acid, copolymers of a methacrylic acid ester and methacrylic acid, copolymers of an acrylic acid ester, a methacrylic acid ester and acrylic acid, copolymers of an acrylic acid ester, a methacrylic acid ester and methacrylic acid, and copolymers of an acrylic acid ester, a methacrylic acid ester, an acrylic acid and a methacrylic acid. Of these, it is preferable to use a copolymer of an acrylic acid ester, a methacrylic acid ester and acrylic acid.
[0082] The weight average molecular weight (Mw) of the acrylic resin is usually from 6,000 to 50,000, preferably from 8,000 to 25,000, and more preferably from 10,000 to 20,000. When the weight average molecular weight (Mw) of the acrylic resin is within the above range, the low temperature fixability can be improved.
[0083] The ratio of the acrylic acid ester monomer unit, the methacrylic acid ester monomer unit, the acrylic acid monomer unit, and the methacrylic acid monomer unit in the acrylic resin can be adjusted by the mass ratio of the amount of the acrylic acid ester, the methacrylic acid ester, the acrylic acid, and the methacrylic acid added during the synthesis of the copolymer. The mass ratio of the amount of the added amount may be, for example, (acrylic acid ester and / or methacrylic acid ester):(acrylic acid and / or methacrylic acid)=(99-99.95):(0.05-1), preferably (acrylic acid ester and / or methacrylic acid ester):(acrylic acid and / or methacrylic acid)=(99.4-99.9):(0.1-0.6), and more preferably (acrylic acid ester and / or methacrylic acid ester):(acrylic acid and / or methacrylic acid)=(99.5-99.7):(0.3-0.5).
[0084] Examples of acrylic esters used to form the acrylic resin include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, sec-pentyl acrylate, isopentyl acrylate, neopentyl acrylate, n-hexyl acrylate, isohexyl acrylate, neohexyl acrylate, sec-hexyl acrylate, and tert-hexyl acrylate, and among these, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, and n-butyl acrylate are preferred, and n-butyl acrylate is more preferred.
[0085] Examples of methacrylic acid esters used to form the acrylic resin include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, sec-pentyl methacrylate, isopentyl methacrylate, neopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, neohexyl methacrylate, sec-hexyl methacrylate, and tert-hexyl methacrylate, and among these, methyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, and n-butyl methacrylate are preferred, and methyl methacrylate is more preferred.
[0086] Although commercially available acrylic resins can be used, the acrylic resins can be produced by known methods such as solution polymerization, aqueous solution polymerization, ionic polymerization, high-temperature high-pressure polymerization, and suspension polymerization.
[0087] The amount of polar resin added is preferably 0.3 to 4 parts by mass, more preferably 0.5 to 3 parts by mass, further preferably 0.6 to 2.5 parts by mass, and particularly preferably 0.7 to 2 parts by mass, relative to 100 parts by mass of binder resin. By setting the amount of polar resin added within the above range, it is possible to obtain a sufficient effect of adding the polar resin while improving environmental stability.
[0088] <Heat mixing process, crushing process> In the pulverization method, the binder resin, colorant, charge control agent, and crystalline material, as well as other additives added as necessary, such as additives having a polydiene structure and polar resins, are mixed using a mixer, such as a ball mill, a V-type mixer, a Henschel mixer (trade name), a high-speed dissolver, an internal mixer, or a Forberg. Next, the mixture obtained above is kneaded while being heated using a pressure kneader, a twin-screw extrusion kneader, a roller, or the like, and then the kneaded product obtained is coarsely pulverized using a pulverizer such as a hammer mill, a cutter mill, or a roller mill. Furthermore, after finely pulverizing using a pulverizer such as a jet mill or a high-speed rotary pulverizer, the particles are classified into desired particle sizes using a classifier such as an air classifier or an airflow classifier to obtain pulverized colored resin particles.
[0089] <Dispersion process> Next, the pulverized colored resin particles obtained above are dispersed in an aqueous dispersion medium to obtain a dispersion of colored resin particles.
[0090] The aqueous dispersion medium used in the dispersion step is obtained by dissolving or dispersing a dispersion stabilizer in an aqueous medium. As the aqueous medium, water may be used alone, but it may also be used in combination with a solvent that is soluble in water. Examples of the solvent that is soluble in water include lower ketones such as dimethylformamide, tetrahydrofuran, acetone, and methyl ethyl ketone.
[0091] The dispersion stabilizer may be any compound capable of imparting dispersibility to disperse the pulverized colored resin particles in an aqueous medium, and is not particularly limited. Examples of the organic dispersion stabilizer include water-soluble polymers such as polyvinyl alcohol, methyl cellulose, and gelatin; surfactants such as anionic surfactants, nonionic surfactants, and amphoteric surfactants; and the like. Examples of the inorganic dispersion stabilizer include metal oxides such as aluminum oxide and titanium oxide; sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate, magnesium phosphate, and aluminum phosphate; metal hydroxides such as aluminum hydroxide, magnesium hydroxide, and ferric hydroxide; inorganic particles such as silica, titanium dioxide, and aluminum oxide; silicone, and metal soaps. Among these, inorganic dispersion stabilizers are preferred, with phosphates or metal hydroxides being more preferred, and metal hydroxides being even more preferred.
[0092] Among inorganic dispersion stabilizers, poorly water-soluble inorganic dispersion stabilizers are preferred, and it is particularly preferred to use poorly water-soluble inorganic dispersion stabilizers in a state where they are dispersed in an aqueous medium in the form of colloidal particles, i.e., in the state of a colloidal dispersion liquid containing poorly water-soluble inorganic dispersion stabilizer colloidal particles. By using poorly water-soluble inorganic dispersion stabilizers in the state of a colloidal dispersion liquid containing poorly water-soluble inorganic dispersion stabilizer colloidal particles, it is possible to narrow the particle size distribution of the colored resin particles, and in addition, the amount of residue in the toner obtained can be easily reduced by washing, which makes it possible to further improve fine line reproducibility and also contributes to environmental stability.
[0093] A colloidal dispersion containing poorly water-soluble inorganic dispersion stabilizer colloidal particles can be prepared, for example, by reacting an alkali metal hydroxide and / or an alkaline earth metal hydroxide with a water-soluble polyvalent metal salt (excluding alkaline earth metal hydroxide) in an aqueous medium.
[0094] Examples of the alkali metal hydroxide include lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. Examples of the alkaline earth metal hydroxide include barium hydroxide, calcium hydroxide, etc.
[0095] The water-soluble polyvalent metal salt may be any water-soluble polyvalent metal salt other than the above-mentioned alkaline earth metal hydroxides, and may include, for example, magnesium metal salts such as magnesium chloride, magnesium phosphate, and magnesium sulfate; calcium metal salts such as calcium chloride, calcium nitrate, calcium acetate, and calcium sulfate; aluminum metal salts such as aluminum chloride and aluminum sulfate; barium salts such as barium chloride, barium nitrate, and barium acetate; zinc salts such as zinc chloride, zinc nitrate, and zinc acetate; and the like. Among these, magnesium metal salts, calcium metal salts, and aluminum metal salts are preferred, magnesium metal salts are more preferred, and magnesium chloride is particularly preferred. The water-soluble polyvalent metal salts may be used alone or in combination of two or more.
[0096] The method of reacting the above-mentioned alkali metal hydroxide and / or alkaline earth metal hydroxide with the above-mentioned water-soluble polyvalent metal salt in an aqueous medium is not particularly limited, but includes a method of mixing an aqueous solution of the alkali metal hydroxide and / or alkaline earth metal hydroxide with an aqueous solution of the water-soluble polyvalent metal salt. In this case, from the viewpoint of being able to suitably control the particle size of the poorly water-soluble metal hydroxide colloid particles, a method of mixing by gradually adding the aqueous solution of the alkali metal hydroxide and / or alkaline earth metal hydroxide to the aqueous solution of the water-soluble polyvalent metal salt while stirring the aqueous solution is preferred.
[0097] The ratio of the alkali metal hydroxide and / or alkaline earth metal hydroxide to the water-soluble polyvalent metal salt is not particularly limited, but the amount of the alkali metal hydroxide and / or alkaline earth metal hydroxide used is preferably an amount such that the chemical equivalent ratio b / a of the chemical equivalent b of the alkali metal hydroxide and / or alkaline earth metal hydroxide to the chemical equivalent a of the water-soluble polyvalent metal salt satisfies the relationship 0.3≦b / a≦1.0, and more preferably an amount such that the chemical equivalent ratio b / a satisfies the relationship 0.4≦b / a≦1.0.
[0098] From the viewpoint of dispersing the pulverized colored resin particles well, the amount of the dispersion stabilizer used is preferably 1 part by mass or more, more preferably 10 to 500 parts by mass, and even more preferably 20 to 300 parts by mass, per 100 parts by mass of the pulverized colored resin particles.
[0099] In the dispersion step, the method for dispersing the colored resin particles in the aqueous dispersion medium is not particularly limited, but a method of adding the colored resin particles to the aqueous dispersion medium and stirring with a stirrer is suitable. In this case, the stirring temperature is not particularly limited, but is preferably 10 to 40°C, more preferably 20 to 30°C, and the stirring time is not particularly limited, but is preferably 1 minute to 2 hours, more preferably 3 minutes to 1 hour.
[0100] Alternatively, in the dispersion step, colored resin particles may be added to an aqueous dispersion medium, and then the colored resin particles may be subjected to a dispersion treatment in the aqueous dispersion medium that produces a cavitation effect, thereby obtaining a dispersion of colored resin particles.
[0101] Dispersion treatment that produces a cavitation effect is a dispersion method that utilizes shock waves that are generated when vacuum bubbles generated in a liquid burst when high energy is applied to the liquid.
[0102] Specific examples of dispersion treatments that can achieve a cavitation effect include ultrasonic dispersion treatments, dispersion treatments using a high-shear stirring device such as an in-line emulsifying disperser, and dispersion treatments using a jet mill. Only one of these dispersion treatments may be performed, or a combination of multiple dispersion treatments may be performed. More specifically, dispersion treatments that can achieve a cavitation effect are preferably performed using an ultrasonic homogenizer, a high-shear stirring device, and a jet mill. These devices may be conventionally known.
[0103] The processing time for the dispersion treatment to obtain the cavitation effect is preferably 1 to 300 minutes, more preferably 5 to 100 minutes, and the processing temperature is preferably 10 to 50°C, more preferably 20 to 40°C.
[0104] <Heating process> Next, the dispersion of the colored resin particles prepared in the above dispersion step is heated at a temperature of not less than the glass transition temperature Tg of the colored resin particles and not more than 95° C. for a heating time of not less than 5 minutes and not more than 10 hours.
[0105] In the present invention, in the dispersion step, a dispersion of colored resin particles is prepared, and the prepared dispersion of colored resin particles is heated under the above-mentioned conditions, whereby the sphericity of the colored resin particles can be suitably improved by the heat treatment, and thus the average circularity of the obtained colored resin particles can be further increased, and furthermore, the domain structure of the crystalline material described later can be more suitably formed in the colored resin particles.
[0106] The heating temperature in the heating step is preferably the glass transition temperature Tg of the colored resin particles or more and 95° C. or less, more preferably a temperature 10° C. higher than the glass transition temperature Tg of the colored resin particles (i.e., Tg+10° C. or more) and 94° C. or less, and even more preferably a temperature 15° C. higher than the glass transition temperature of the colored resin particles (i.e., Tg+20° C. or more) and 93° C. or less. The specific heating temperature in the heating step is not particularly limited, but is preferably 40 to 90° C., more preferably 45 to 85° C., even more preferably 50 to 80° C., and particularly preferably 55 to 75° C. The heating time in the heating step is preferably 5 minutes or more and 10 hours or less, more preferably 10 minutes or more and 10 hours or less, and even more preferably 30 minutes or more and 8 hours or less.
[0107] The dispersion of colored resin particles that has been subjected to the heat treatment under the above conditions in the heating step is preferably subjected to a series of operations of washing, filtering, dehydrating, and drying in a conventional manner, which are repeated several times as necessary.
[0108] First, in order to remove the dispersion stabilizer remaining in the dispersion of the colored resin particles after the heat treatment, it is preferable to add an acid or an alkali to the dispersion of the colored resin particles after the heat treatment and wash them. When the dispersion stabilizer used is an acid-soluble compound, it is preferable to add an acid to the dispersion of the colored resin particles and wash them, while when the dispersion stabilizer used is an alkali-soluble compound, it is preferable to add an alkali to the dispersion of the colored resin particles after the heat treatment and wash them.
[0109] Furthermore, when an acid-soluble compound is used as the dispersion stabilizer, it is preferable to add an acid to the aqueous dispersion of the colored resin particles after the heat treatment to adjust the pH to preferably 6.5 or less, more preferably 6 or less. The acid to be added may be an inorganic acid such as sulfuric acid, hydrochloric acid, or nitric acid, or an organic acid such as formic acid or acetic acid, but sulfuric acid is particularly preferable because it has a high efficiency of removing the dispersion stabilizer and places a small burden on the production equipment.
[0110] The dehydration and filtration methods can be any of various known methods, and are not particularly limited. For example, centrifugal filtration, vacuum filtration, pressure filtration, etc. The drying method is also not particularly limited, and various methods can be used.
[0111] In the present invention, it is preferable to provide a preheating step of preheating the dispersion of colored resin particles obtained in the dispersing step before the heating step. In this case, it is preferable to subject the dispersion of colored resin particles that has been subjected to the preheating step to a heat treatment in the heating step.
[0112] The preheating temperature in the preheating step is preferably a temperature 10 to 1°C lower than the glass transition temperature Tg of the colored resin particles (Tg-10 to Tg-1°C) and a temperature 10°C or more lower than the melting point mp of the crystalline material (mp-10°C or lower), and more preferably a temperature 8 to 2°C lower than the glass transition temperature Tg of the colored resin particles (Tg-8 to Tg-2°C) and a temperature 8 to 5°C lower than the melting point mp of the crystalline material (mp-8 to mp-5°C). The preheating time is preferably 30 minutes or more and 10 hours or less, and more preferably 60 minutes or more and 5 hours or less. By setting the preheating temperature and preheating time in the above ranges, it is possible to more suitably form a domain structure of the crystalline material described later in the colored resin particles.
[0113] In this manner, the colored resin particles constituting the toner of the present invention can be produced.
[0114] In the above, a method for producing the colored resin particles constituting the toner of the present invention using a pulverization method, which is an example of a dry method, has been exemplified. However, the colored resin particles constituting the toner of the present invention may be produced by a wet method, for example, a suspension polymerization method, which is an example of a wet method.
[0115] In the suspension polymerization method, the colored resin particles constituting the toner of the present invention are produced as follows. First, a polymerizable monomer, a colorant, a charge control agent, and a crystalline material, as well as other additives added as necessary, are mixed and dissolved to prepare a polymerizable monomer composition. Then, the polymerizable monomer composition is dispersed in an aqueous dispersion medium, a polymerization initiator is added, and droplets of the polymerizable monomer composition are formed to obtain a suspension of the polymerizable monomer composition. Next, the obtained suspension of the polymerizable monomer composition is heated to initiate polymerization, thereby obtaining an aqueous dispersion of colored resin particles containing a binder resin, a colorant, a charge control agent, and a crystalline material. A series of operations of washing, filtration, dehydration, and drying are repeated several times as necessary to produce the colored resin particles constituting the toner of the present invention.
[0116] The colored resin particles constituting the toner of the present invention, when the cross section is observed by the reflected electron image of a scanning electron microscope, the total area ratio of the domains of the crystalline material in the cross section of the colored resin particles observed by the reflected electron image of a scanning electron microscope is 10 to 30%, and the number of domains of the crystalline material in the cross section of the colored resin particles observed by the reflected electron image of a scanning electron microscope is in the range of 10 to 40 on average per particle. According to the present invention, by making the total area ratio of the domains of the crystalline material and the number of domains of the crystalline material contained in the colored resin particles constituting the toner as described above, the toner obtained has excellent low-temperature fixing properties, is well-balanced in hot offset resistance, fine line reproducibility, and blade cleaning properties, and further, is appropriately suppressed from being ejected after being left at high temperatures.
[0117] FIG. 1 shows a cross-sectional photograph of the colored resin particles obtained in Example 6 described later, taken by a backscattered electron image of a scanning electron microscope (FE-SEM). As shown in FIG. 1, the colored resin particles of the present invention have a structure in which domains of crystalline material (the dark parts in FIG. 1) are dispersed in the colored resin particles. In the present invention, the total area ratio of the domains of crystalline material in the cross section of the colored resin particles observed by the backscattered electron image of a scanning electron microscope (i.e., the ratio of the area of the domains of crystalline material to the cross section area of the colored resin particles) is set to a range of 10 to 30%. The total area ratio of the domains of crystalline material is preferably 15 to 28%, more preferably 18 to 26%.
[0118] In addition, in the present invention, the number of domains of the crystalline material present in the cross section of the colored resin particle observed in a backscattered electron image of a scanning electron microscope is set to be in the range of 5 to 40 on average per particle. The number of domains of the crystalline material present is preferably 10 to 35, more preferably 15 to 30.
[0119] The total area ratio of the domains of the crystalline material and the number of domains of the crystalline material in the cross section of the colored resin particle observed by the backscattered electron image of the scanning electron microscope can be measured, for example, by the following method. That is, first, the colored resin particles are mixed with a curable material such as a two-liquid condensation type epoxy adhesive, and cured to prepare a cured product, and the prepared cured product is cut using a microtome or the like to prepare a sample for cross-section observation. Next, the prepared sample for cross-section observation is measured by a backscattered electron image using a scanning electron microscope to observe the cross section of the colored resin particle. In addition, at this time, it is desirable to adjust the measurement conditions so that the domains of the crystalline material are easily observed.
[0120] Then, the cross-sectional photograph of the colored resin particles obtained by the measurement of the reflected electron image of the scanning electron microscope is subjected to image analysis using image analysis software (for example, "DNP Particle Image Analysis Software" (manufactured by Dai Nippon Printing Co., Ltd.) etc.), so that the total area ratio of the crystalline material domains and the number of crystalline material domains present can be obtained. Specifically, the total area ratio of the crystalline material domains can be calculated by measuring 100 or more colored resin particles, determining the total area of the colored resin particles and the total area of the crystalline material domain parts by image analysis, and using these. In addition, the number of crystalline material domains present can be calculated by measuring 100 or more colored resin particles, determining the number of the colored resin particles measured and the total number of crystalline material domain parts, and using these. In addition, the measurement targets are colored resin particles whose particle diameter is within ±3 μm of the volume average particle diameter (Dv) of the colored resin particles measured by a particle size analyzer using a Coulter counter, and the above measurement is performed (i.e., colored resin particles whose particle diameter deviates from the volume average particle diameter (Dv) by more than ±3 μm are not measured).
[0121] The method for setting the total area ratio of the domains of the crystalline material and the number of domains of the crystalline material in the cross section of the colored resin particles observed in a backscattered electron image of a scanning electron microscope within the above range is not particularly limited, but examples thereof include a method of adjusting the type and amount of the crystalline material used, a method of adding an additive having a polydiene structure to the colored resin particles, a method of carrying out the above-mentioned dispersion process and heating process when producing the colored resin particles, and a method of appropriately combining the above-mentioned method of carrying out a preheating process.
[0122] In addition, in the colored resin particles of the present invention, the total area ratio of the domains of the crystalline material and the number of domains of the crystalline material are within the above ranges, and the shape of the domains of the crystalline material is preferably as follows. That is, in the colored resin particles of the present invention, the average circularity of the domains of the crystalline material in the cross section of the colored resin particles observed by the backscattered electron image of a scanning electron microscope is preferably 0.50 or less, more preferably 0.10 to 0.47, and even more preferably 0.20 to 0.45. In addition, in the colored resin particles of the present invention, the average value of the ratio of the minor axis to the major axis of the domains of the crystalline material in the cross section of the colored resin particles observed by the backscattered electron image of a scanning electron microscope is preferably 0.60 or less, more preferably 0.15 to 0.50, and even more preferably 0.25 to 0.40. When either one or both of the average circularity and the average value of the ratio of the minor axis to the major axis of the domains of the crystalline material are within the above ranges, the effect of the present invention can be further improved.
[0123] The average circularity of the crystalline material domains and the average ratio of the minor axis to the major axis of the crystalline material domains in the cross section of the colored resin particle observed by the reflected electron image of a scanning electron microscope can be measured, for example, in the same manner as in the case of the total area ratio of the crystalline material domains and the number of crystalline material domains described above, by preparing a sample for cross-sectional observation and measuring the prepared sample for cross-sectional observation by a scanning electron microscope using a reflected electron image to observe the cross section of the colored resin particle.
[0124] Then, the cross-sectional photograph of the colored resin particles obtained by the measurement of the reflected electron image of the scanning electron microscope can be analyzed by image analysis software in the same manner as described above. Specifically, the average circularity of the domains of the crystalline material can be obtained by measuring 100 or more colored resin particles, specifying the shape of the domain part of the crystalline material for each domain part, calculating the circularity from the specified shape of the domain part, and averaging the obtained results. The average ratio of the minor axis to the major axis of the domains of the crystalline material can be obtained by measuring 100 or more colored resin particles, measuring the major axis and minor axis for each domain part, calculating the ratio of the minor axis to the major axis (= minor axis / major axis) based on the measured values, and averaging the obtained results. In addition, in the measurement, the colored resin particles having a particle diameter within ±3 μm of the volume average particle diameter (Dv) of the colored resin particles measured by the Coulter counter are measured as the measurement objects, and the above measurement is performed.
[0125] The method for adjusting the average circularity of the domains of the crystalline material and the average ratio of the minor axis to the major axis of the domains of the crystalline material in the cross section of the colored resin particles observed in a backscattered electron image of a scanning electron microscope to the above range is not particularly limited, and examples thereof include a method of adjusting the type and amount of the crystalline material used, a method of adding an additive having a polydiene structure to the colored resin particles, a method of carrying out the above-mentioned dispersion process and heating process when producing the colored resin particles, and a method of appropriately combining the above-mentioned method and a method of carrying out a preheating process.
[0126] The average circularity of the colored resin particles constituting the toner of the present invention is not particularly limited, but is preferably 0.950 to 1.000, more preferably 0.955 to 0.995, and further preferably 0.960 to 0.995.
[0127] From the viewpoint of image reproducibility, the volume average particle diameter (Dv) of the colored resin particles is preferably 5.0 to 12 μm, more preferably 5.5 to 10 μm, and even more preferably 6.0 to 9.0 μm. By setting the volume average particle diameter (Dv) of the colored resin particles in the above range, the toner fluidity can be improved while appropriately suppressing deterioration of image quality and reduction in image resolution due to fogging and the like.
[0128] The particle size distribution (Dv / Dp), which is the ratio of the volume average particle size (Dv) to the number average particle size (Dp) of the spherical colored resin particles, is preferably 1.00 to 1.40, more preferably 1.10 to 1.30, even more preferably 1.11 to 1.25, and particularly preferably 1.13 to 1.20. The volume average particle size (Dv) and number average particle size (Dp) of the spherical colored resin particles can be measured, for example, using a particle size analyzer using a Coulter counter (manufactured by Beckman Coulter, product name: Multisizer).
[0129] The colored resin particles may be used as a toner as is or by mixing the colored resin particles with carrier particles (ferrite, iron powder, etc.); however, in order to adjust the chargeability, fluidity, storage stability, etc. of the toner, an external additive may be added and mixed with the colored resin particles using a high-speed mixer (for example, FM Mixer (product name, manufactured by Nippon Coke & Engineering Co., Ltd.)) to form a one-component toner, or the colored resin particles, an external additive, and carrier particles may be mixed to form a two-component toner.
[0130] The agitator used for the external addition treatment is not particularly limited as long as it is a stirring device that can adhere an external additive to the surface of the colored resin particles, and the external addition treatment can be performed using an agitator capable of mixing and stirring, such as FM Mixer (product name, manufactured by Nippon Coke and Engineering Co., Ltd.), Super Mixer (product name, manufactured by Kawada Manufacturing Co., Ltd.), Q Mixer (product name, manufactured by Nippon Coke and Engineering Co., Ltd.), Mechanofusion System (product name, manufactured by Hosokawa Micron Corporation), or Mechano Mill (product name, manufactured by Okada Seiko Co., Ltd.).
[0131] Examples of the external additive include inorganic fine particles made of silica, titanium oxide, aluminum oxide, zinc oxide, tin oxide, calcium carbonate, calcium phosphate, and cerium oxide; and organic fine particles made of polymethyl methacrylate resin, silicone resin, and melamine resin. Among these, inorganic fine particles are preferred, silica and titanium oxide are more preferred, and silica is particularly preferred. In addition, it is preferred to use two or more types of fine particles in combination as the external additive. Although each of these external additives can be used alone, it is preferred to use two or more types in combination.
[0132] The external additive is preferably used in an amount of 0.3 to 6 parts by mass, and more preferably 1.2 to 3 parts by mass, based on 100 parts by mass of the colored resin particles.
[0133] The toner of the present invention uses colored resin particles in which the total area ratio of crystalline material domains and the number of crystalline material domains present in the cross section of the colored resin particles observed in a reflected electron image of a scanning electron microscope are within the above-mentioned ranges, and therefore has a well-balanced excellent offset resistance, fine line reproducibility and blade cleanability, and the occurrence of toner ejection after being left at high temperatures is suppressed. EXAMPLES
[0134] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Note that "parts" and "%" are by weight unless otherwise specified. The test methods used in the present examples and comparative examples are as follows.
[0135] (1) Glass transition temperature The glass transition temperature was measured according to ASTM D3418-82.
[0136] (2) Volume average particle size of colored resin particles Dv The volume average particle diameter Dv of the colored resin particles was measured using a particle size measuring instrument (manufactured by Beckman Coulter, Inc., product name: Multisizer) using a Coulter counter. The measurement using this Multisizer was performed under the following conditions: aperture diameter: 100 μm, dispersion medium: Isoton II (product name), concentration: 10%, number of particles measured: 100,000. Specifically, 0.2 g of colored resin particles were placed in a beaker, and a surfactant aqueous solution (manufactured by Fujifilm Corporation, product name: Drywell) was added as a dispersant. 2 ml of dispersion medium was further added to wet the colored resin particles, and then 10 ml of dispersion medium was added. The particles were dispersed in an ultrasonic disperser for 1 minute, and then the particle size was measured using the particle size measuring device.
[0137] (3) Average circularity of colored resin particles 10 ml of ion-exchanged water was placed in a container, 0.2 g of a surfactant aqueous solution (manufactured by Fujifilm Corporation, product name: Drywell) was added as a dispersant, and 0.2 g of colored resin particles were added, and a dispersion process was performed for 3 minutes at 60 W using an ultrasonic disperser. The colored resin particle concentration at the time of measurement was adjusted to 3,000 to 10,000 particles / μL, and 1,000 to 10,000 colored resin particles with a circle equivalent diameter of 0.4 μm or more were measured using a flow-type particle image analyzer (manufactured by Sysmex Corporation, product name: FPIA-2100). The average circularity was calculated from the measured value. The circularity is expressed by the following formula, and the average circularity is the average value thereof. (Circularity) = (perimeter of a circle equal to the projected area of a particle) / (perimeter of the projected image of a particle)
[0138] (4) Microstructure of the domains of crystalline material in the cross section of a colored resin particle as seen in a backscattered electron image taken with a scanning electron microscope The colored resin particles were mixed with a two-liquid condensation type epoxy adhesive and cured to produce a cured product, which was then cut using a microtome or the like to produce a sample for cross-sectional observation. Next, the cross-section of the colored resin particles was observed by measuring the backscattered electron image of the prepared sample for cross-sectional observation using a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-7610F). Note that the measurement conditions were adjusted so that the domains of the crystalline material could be easily observed. Then, the cross-sectional photograph of the colored resin particles obtained by the measurement of the reflected electron image of the scanning electron microscope was analyzed using image analysis software (DNP particle image analysis software, manufactured by Dai Nippon Printing Co., Ltd.) to measure the total area ratio of the crystalline material domains, the number of crystalline material domains (average number per particle), the average circularity of the crystalline material domains, and the average ratio of the minor axis to the major axis of the crystalline material domains. Note that at this time, the measurement targets were 100 or more colored resin particles whose particle diameter was within ±3 μm of the volume average particle diameter (Dv) of the colored resin particles. The total area ratio of the crystalline material domains was determined by calculating the total area of the colored resin particles and the total area of the crystalline material domain portions, and then calculating the area ratio of the crystalline material domains in the cross section of the colored resin particles from these results. The number of domains of the crystalline material (average number per particle) was calculated by determining the number of colored resin particles being measured and the total number of domain portions of the crystalline material, and then dividing the total number of domain portions of the crystalline material by the number of colored resin particles. The average circularity of the domains of the crystalline material was determined by identifying the shape of each domain portion of the crystalline material, calculating the circularity from the identified shape of the domain portion, and averaging the results. The average ratio of the short diameter to the long diameter of the domains of the crystalline material was obtained by measuring the long diameter and short diameter of each domain, calculating the ratio of the short diameter to the long diameter (= short diameter / long diameter) based on this, and averaging the results.
[0139] (5) Minimum fixing temperature of toner A fixing test was conducted using a commercially available non-magnetic single-component development printer (printing speed 20 ppm) modified to change the temperature of the fixing roll. The fixing test was conducted by printing a solid black image (100% print density) and changing the temperature of the fixing roll of the modified printer by 5°C increments, measuring the toner fixing rate at each temperature, and determining the relationship between temperature and fixing rate. The fixing rate was calculated from the ratio of image density before and after tape peeling by peeling off tape in the printed area of the solid black image (100% print density). In other words, if the image density before tape peeling is ID (before) and the image density after tape peeling is ID (after), the fixing rate can be calculated by the following formula. Retention rate (%) = (ID (later) / ID (previous)) x 100 Here, the tape peeling operation refers to a series of operations in which an adhesive tape (manufactured by Sumitomo 3M, product name: Scotch Mending Tape 810-3-18) is applied to the measurement portion of the test paper, pressed with a constant pressure to adhere, and then the adhesive tape is peeled off in the direction along the paper at a constant speed. The image density was measured using a reflection type image densitometer (manufactured by Macbeth, product name: RD914). In this fixing test, the lowest fixing roll temperature at which the fixing rate exceeded 80% was determined as the minimum fixing temperature of the toner.
[0140] (6) Hot offset resistance A hot offset test was conducted using a commercially available non-magnetic single-component development printer (24 sheets; print speed = 24 sheets / min) modified to change the temperature of the fixing roll. The hot offset test was conducted by changing the temperature of the fixing roll from 150°C to 100°C in 5°C increments, printing a 5cm square solid image on paper (Xerox, product name: Vitality), and visually observing whether the toner had melted onto the fixing roll or whether the hot offset phenomenon had occurred. In this hot offset test, it was confirmed whether or not toner had melted onto the fixing roll. If no toner had melted onto the fixing roll even after heating to 200°C, it was marked as "O", and if toner had melted onto the fixing roll, it was marked as "X".
[0141] (7) Eruption after high-temperature storage A commercially available non-magnetic single-component development toner cartridge was filled with toner and then left in an environment of 50° C. for 120 hours. After leaving it, continuous printing was performed for 2 hours using a commercially available non-magnetic single-component development printer, and the toner was visually checked for any ejection, and evaluated according to the following criteria. ◎: There was no spillage at all. ○: There was a slight amount of ink spilling from one part of the developing machine. △: There was slight spraying from the entire surface of the developing machine.
[0142] (8) Fine line reproducibility The toner was placed in a commercially available printer using a non-magnetic single-component development method, and after leaving it for one day under an N / N environment, a line image was continuously formed in 2 x 2 dot lines (width approximately 85 μm) and 10,000 sheets were printed. The moving speed of the photoconductor surface at the position where it contacted the cleaning blade was 12 cm / sec. Every 500 sheets of print, the print evaluation system (manufactured by YA-MA, product name: RT2000) was used to measure and obtain density distribution data of the line image. At this time, the full width at half the maximum density was taken as the line width, and the line width of the first sheet of line image was taken as the standard. If the difference in line width was 10μm or less, it was considered that the first sheet of line image was reproduced. The number of sheets that could maintain the difference in line width of 10μm or less was investigated, and the grades were divided into three categories: "◎" for maintaining the thin line for 10,000 sheets or more, "○" for maintaining the thin line for 7,000 sheets or more but less than 10,000 sheets, and "△" for maintaining the thin line for 5,000 sheets or more but less than 7,000 sheets.
[0143] (9) Blade cleaning ability A test cleaning blade sample was attached to the printer described above in (8), toner was put into the cartridge, printing paper was set, and the printer was left overnight under N / N conditions. After that, continuous printing was performed at 5% density from the beginning, and the photoconductor and charging roll were visually observed every 500 sheets printed to test whether streaks (filming) due to cleaning failure occurred, and the presence or absence of cleaning failure was tested up to 10,000 sheets printed. The test results were shown in the number of printed sheets on which cleaning failure occurred. The results were classified into three levels: "◎" for those who did not experience cleaning failure even after printing 10,000 sheets or more continuously, "〇" for those who could print 7,000 sheets or more continuously but had cleaning failure by 10,000 sheets, and "△" for those who could print 5,000 sheets or more continuously but had cleaning failure by 7,000 sheets.
[0144] [Production Example 1, Production of Styrene-Butyl Acrylate Copolymer (α-1) (Binder Resin)] After adding 0.2 parts of a nonionic dispersant ("PVA235" manufactured by Kuraray Co., Ltd.) to 200 parts of ion-exchanged water, a monomer mixture consisting of 86 parts of styrene and 14 parts of butyl acrylate and a polymerization initiator (benzoyl peroxide) were added, and the mixture was maintained at 130°C for 2 hours with stirring to carry out suspension polymerization, thereby obtaining a copolymer suspension. The resulting suspension was cooled to 30°C, dehydrated using a centrifugal dehydrator, and dried at 50°C for 24 hours to obtain a styrene-butyl acrylate copolymer (α-1). The resulting styrene-butyl acrylate copolymer (α-1) was composed of 86% styrene units and 14% butyl acrylate units, and had a glass transition temperature Tg of 54°C.
[0145] [Production Example 2, Production of Block Copolymer Composition (β-1) (Additive Having Polydiene Structure)] In a pressure-resistant reactor, 23.2 kg of cyclohexane, 1.5 mmol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as TMEDA), and 1.70 kg of styrene were added, and while stirring at 40°C, 99.1 mmol of n-butyllithium was added, and polymerization was carried out for 1 hour while raising the temperature to 50°C. The polymerization conversion rate of styrene was 100% by mass. Subsequently, 6.03 kg of isoprene was continuously added to the reactor over 1 hour while controlling the temperature to maintain 50-60°C. After the addition of isoprene was completed, polymerization was carried out for another 1 hour to form a styrene-isoprene diblock copolymer B (copolymer B represented by Ar-D). The polymerization conversion rate of isoprene was 100%. Next, 15.0 mmol of dimethyldichlorosilane was added as a coupling agent to carry out a coupling reaction for 2 hours, and a styrene-isoprene-styrene triblock copolymer (copolymer A represented by Ar-D-Ar) was formed. After that, 198 mmol of methanol was added as a polymerization terminator and mixed well to stop the reaction, thereby obtaining a reaction liquid containing a block copolymer composition (β-1). A part of the obtained reaction liquid was taken out, and the weight average molecular weight, content ratio, and vinyl bond content of each block copolymer and the entire block copolymer composition were determined. The obtained results are shown in Table 1. Then, 0.3 parts of 2,6-di-tert-butyl-p-cresol was added as an antioxidant to 100 parts of the reaction liquid obtained in this way (containing 30 parts of polymer component) and mixed, and the mixed solution was dropped into hot water heated to 85 to 95 ° C. in small amounts to volatilize the solvent and obtain a precipitate, which was crushed and dried with hot air at 85 ° C. to recover the block copolymer composition (β-1). The melt index of the obtained block copolymer composition (β-1) was measured, and the obtained results are shown in Table 1.
[0146] [Production Example 3, Production of colloidal dispersion containing magnesium hydroxide colloidal particles] A colloidal dispersion containing magnesium hydroxide colloidal particles was prepared by gradually adding, with stirring for 10 minutes, an aqueous solution of 7.3 parts of sodium hydroxide in 50 parts of ion-exchanged water to an aqueous solution of 10.4 parts of magnesium chloride in 280 parts of ion-exchanged water.
[0147] [Table 1]
[0148] [Example 1] (Production of colored resin particles) As a binder resin, 100 parts of styrene-butyl acrylate copolymer (α-1) obtained in Production Example 1, 5 parts of carbon black (manufactured by Mitsubishi Chemical Corporation, product name: MA-100) as a colorant, 20 parts of behenyl stearate (melting point: 69.2°C, number average molecular weight 592) as an ester wax as a crystalline material, 5 parts of block copolymer composition (β-1) (additive having a polydiene structure) obtained in Production Example 2, and 5 parts of a charge control resin (manufactured by Fujikura Chemical Industries, quaternary ammonium base-containing styrene acrylic resin, functional group amount 4%) as a charge control agent were mixed in a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd., product name: FM20B). Next, the obtained mixture was melt-kneaded using a twin-screw extruder, and the obtained kneaded product was cooled. Next, the cooled mixture was pulverized using a mechanical pulverizer (Turbo Kogyo Co., Ltd., product name: Turbo Mill) and classified using an elbow jet classifier (Nippon Steel Mining Co., Ltd., product name: EJ-LABO) to obtain pulverized irregular colored resin particles with a number-volume average particle diameter of 7.1 μm (heating and kneading process, pulverization process).
[0149] Next, a mixed solution of 4.0 parts of the colloidal dispersion containing the magnesium hydroxide colloidal particles obtained in Production Example 3 and 400.0 parts of ion-exchanged water was added to 10 parts of the crushed colored resin particles obtained above, and stirred to obtain a dispersion of colored resin particles (dispersion step). Next, a sample tube containing a stirrer was placed in a thermostatic water bath set at a temperature of 50°C, and the dispersion of colored resin particles obtained above was placed in the sample tube, and the mixture was left to stand for 120 minutes while slowly stirring, thereby performing preheating, and obtaining a dispersion of colored resin particles after preheating (preheating step). Next, a sample tube containing a stirrer was placed in a thermostatic water bath set at 70°C, and the dispersion of colored resin particles obtained above after preheating was placed in the sample tube, and the mixture was left to stand for 30 minutes while slowly stirring, thereby performing a heat treatment of the dispersion of colored resin particles after preheating, thereby making the colored resin particles spherical (heating step).
[0150] Next, while stirring the dispersion of the colored resin particles after the heat treatment, sulfuric acid was added until the pH became 4.5, and acid washing was performed under conditions of a temperature of 25°C for 10 minutes, and then the colored resin particles were filtered out by filtration, washed with water, and the washing water was filtered. The electrical conductivity of the filtrate at this time was 11 μS / cm. Furthermore, the colored resin particles after washing and filtration were dehydrated and dried to obtain colored resin particles in a dry state. Then, using the obtained colored resin particles, each of the volume average particle size Dv, average circularity, and the microstructure of the domain of the crystalline material in the cross section of the colored resin particles by the backscattered electron image of a scanning electron microscope was measured. The results are shown in Table 2. The glass transition temperature of the colored resin particles was almost equal to the glass transition temperature of the binder resin (the same applies to Examples 2 to 8 and Comparative Examples 1 to 3 described later).
[0151] (Toner manufacturing) 0.5 parts of silica fine particles (manufactured by Nihon Aerosil Co., Ltd., product name: RX-200) having a volume average particle size of 12 nm, which had been hydrophobized with hexamethyldisilazane, 2.0 parts of silica fine particles (manufactured by Nihon Aerosil Co., Ltd., product name: RX-50) having a volume average particle size of 40 nm, which had been hydrophobized with hexamethyldisilazane, and 0.5 parts of titanium oxide fine particles (manufactured by Titan Kogyo Co., Ltd., product name: EC-300, volume average particle size: 0.3 μm) having a specific resistance of 40 Ω·cm and surface-treated with antimony-doped tin oxide were added to 100 parts of the colored resin particles obtained above, and the mixture was mixed for 10 minutes at a rotation speed of 3000 rpm using a Henschel mixer to obtain a toner. The obtained toner was then evaluated for minimum fixing temperature, hot offset resistance, ejection after high-temperature storage, fine line reproducibility, and blade cleaning properties. The results are shown in Table 2.
[0152] [Example 2] Except for changing the amount of behenyl stearate used as the ester wax to 30 parts, colored resin particles and a toner were obtained and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0153] [Example 3] Except for changing the amount of behenyl stearate used as the ester wax to 40 parts, colored resin particles and a toner were obtained and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0154] [Example 4] Except for changing the amount of behenyl stearate used as the ester wax to 10 parts, colored resin particles and a toner were obtained and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0155] [Example 5] Except for using 30 parts of pentaerythritol tetrapalmitate (melting point: 71.0°C, number average molecular weight: 1088) as the ester wax instead of behenyl stearate as the ester wax, colored resin particles and toner were obtained and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0156] [Example 6] Except for using 30 parts of pentaerythritol tetrastearate (melting point: 76.0°C, number average molecular weight: 1200) as the ester wax instead of behenyl stearate as the ester wax, colored resin particles and toner were obtained and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0157] [Example 7] Except for changing the amount of the block copolymer composition (β-1) obtained in Production Example 2 to 15 parts, colored resin particles and a toner were obtained and evaluated in the same manner as in Example 2. The results are shown in Table 2.
[0158] [Example 8] Except for changing the amount of the block copolymer composition (β-1) obtained in Production Example 2 to 1 part, colored resin particles and a toner were obtained and evaluated in the same manner as in Example 2. The results are shown in Table 2.
[0159] [Comparative Example 1] Colored resin particles and a toner were obtained and evaluated in the same manner as in Example 2, except that the block copolymer composition (β-1) obtained in Production Example 2 was not used. The results are shown in Table 2.
[0160] [Comparative Example 2] Except for changing the amount of behenyl stearate used as the ester wax to 5 parts, colored resin particles and a toner were obtained and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0161] [Comparative Example 3] 78 parts of styrene and 22 parts of n-butyl acrylate as polymerizable monomers, and 5 parts of carbon black (manufactured by Mitsubishi Chemical Corporation, product name: #25B) as a black colorant were dispersed using an in-line emulsifying disperser (manufactured by Pacific Machinery Works, product name: Milder) to obtain a polymerizable monomer mixture.
[0162] To the polymerizable monomer mixture obtained above, 1.0 part of a charge control resin (styrene acrylic resin containing a quaternary ammonium group) as a charge control agent, 30 parts of behenyl stearate as an ester wax, 1 part of the block copolymer composition (β-1) (additive having a polydiene structure) obtained in Production Example 2, 0.6 parts of divinylbenzene as a crosslinkable polymerizable monomer, and 1.6 parts of t-dodecyl mercaptan as a molecular weight regulator were added, mixed, and dissolved to prepare a suspension in which the polymerizable monomer composition was dispersed (polymerizable monomer composition dispersion).
[0163] The polymerizable monomer composition dispersion liquid prepared above was put into a reactor equipped with an agitator, and the temperature was raised to 90°C to initiate the polymerization reaction. When the polymerization conversion rate reached almost 100%, 1 part of methyl methacrylate as a shell polymerizable monomer and 0.3 parts of 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide) (trade name: VA-086, manufactured by Wako Pure Chemical Industries, Ltd., water-soluble) as a shell polymerization initiator dissolved in 10 parts of ion-exchanged water were added, and the reaction was continued at 90°C for 4 hours, and then the reaction was stopped by cooling with water to obtain an aqueous medium dispersion liquid containing colored resin particles having a core-shell structure.
[0164] Sulfuric acid was added dropwise to the aqueous dispersion of colored resin particles obtained above while stirring at room temperature, and acid washing was performed until the pH became 6.5 or less. Then, filtration and separation were performed, and 500 parts of ion-exchanged water was added to the obtained solid matter to reslurry it, and water washing treatment (washing, filtration, dehydration) was repeated several times. Then, filtration and separation were performed, and the obtained solid matter was placed in a container of a dryer and dried at 45°C for 48 hours to obtain dried colored resin particles. Then, evaluation was performed in the same manner as in Example 1 using the obtained colored resin particles. The results are shown in Table 2.
[0165] Moreover, a toner was obtained using the colored resin particles obtained above in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.
[0166] [Table 2]
[0167] As shown in Table 2, in Examples 1 to 8, in which the total area ratio of the domains of the crystalline material in the cross section of the colored resin particle observed in the backscattered electron image of a scanning electron microscope is 10 to 30%, and the number of domains of the crystalline material is in the range of 10 to 40 on average per particle, the toner obtained has excellent low-temperature fixing property, is well-balanced in hot offset resistance, fine line reproducibility, and blade cleanability, and is suppressed from spewing out after being left at high temperature. Figure 1 shows a cross-sectional photograph of the colored resin particle of Example 6 taken by the backscattered electron image of a scanning electron microscope.
[0168] On the other hand, in Comparative Examples 1 to 3, in which the total area ratio of the crystalline material domains or the number of crystalline material domains in the cross section of the colored resin particle observed in the backscattered electron image of a scanning electron microscope was outside the scope of the present invention, the hot offset resistance, fine line reproducibility, and blade cleanability were poor, and toner ejection occurred after leaving at high temperatures.
Claims
1. A toner for developing electrostatic images, comprising a binder resin, a colorant, a charge control agent, and colored resin particles containing a crystalline material, When a cross section of the colored resin particle is observed using a backscattered electron image of a scanning electron microscope, a total area ratio of domains of the crystalline material in the cross section of the colored resin particle is 10 to 30%, and the number of domains of the crystalline material present in the cross section of the colored resin particle is in the range of 5 to 40 in terms of the average number present per particle.
2. 2. The toner for developing electrostatic images according to claim 1, wherein, when a cross section of the colored resin particle is observed using a backscattered electron image of a scanning electron microscope, an average circularity of the domains of the crystalline material in the cross section of the colored resin particle is 0.50 or less.
3. 3. The toner for developing electrostatic images according to claim 1, wherein, when a cross section of the colored resin particle is observed using a backscattered electron image of a scanning electron microscope, the average ratio of the minor axis to the major axis of the domain of the crystalline material in the cross section of the colored resin particle is 0.60 or less.
4. 4. The toner for developing electrostatic images according to claim 1, wherein the content of the crystalline material is 5.0 to 40.0 parts by mass based on 100 parts by mass of the binder resin.
5. 5. The toner for developing electrostatic images according to claim 1, wherein the crystalline material is an ester wax having a number average molecular weight (Mn) of 500 to 1,550.
6. 6. The toner for developing electrostatic images according to claim 1, wherein the colored resin particles further contain an additive having a polydiene structure.
7. 7. The toner for developing electrostatic images according to claim 1, wherein the binder resin is a styrene-(meth)acrylic acid ester copolymer.
8. 8. The toner for developing electrostatic images according to claim 1, which is a positively charged toner.
9. 9. The toner for developing electrostatic images according to claim 1, which is produced by a pulverization method or a suspension polymerization method.
Citation Information
Patent Citations
toner
JP2021005050A